Monitoring volcano deformation at La Soufrière, St Vincent during the 2020–21 eruption with insights into its magma plumbing system architecture - Camejo Harry, Michal (2024)
Measurements of surface deformation provide valuable insight into sub-volcanic processes operating before, during and after eruptions. Here, we investigate the drivers behind the 2020-21 effusive-explosive episode at La Soufrière volcano in St. Vincent using Global Positioning System (GPS) and Interferometric Synthetic Aperture Radar (InSAR) data between 2018 and 2021, and geodetic modelling. We observe inflation up to six months before the start to the effusive phase, which continued as the dome extruded. Once the eruption transitioned to the explosive phase, the volcano rapidly deflated, the bulk happening within the first three days of explosions. Our analytical modelling distinguishes three pressure source depth ranges contributing to this eruptive episode: 16 - 20, ∼6 and <1 kilometres. Deformation data are therefore in line with a vertically extensive magmatic system being tapped pre- and syn-eruption with interaction between deep and shallow reservoirs by ascending magma batches. The combined use of GPS and InSAR proved to be instrumental for constraining the deformation field active during this eruptive episode. The direction of future geodetic monitoring at La Soufrière should therefore utilise both techniques with a view towards maximising coverage while making up for shortfalls in station upkeep and variations in satellite overpass regularity.